2005
DOI: 10.1177/10634266050130010301
|View full text |Cite
|
Sign up to set email alerts
|

The Special Education Elementary Longitudinal Study and the National Longitudinal Transition Study

Abstract: The purposes of this article are to (a) describe the design features of two longitudinal studies,the Special Education Elementary Longitudinal Study (SEELS) and the National Longitudinal Transition Study—2 (NLTS2) and (b) outline their potential implications for policy, practice, research, advocacy, and system development for children and youth with emotional disturbances (ED). We begin by reviewing the role of longitudinal research and its importance in building the knowledge base regarding these children and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 142 publications
(116 citation statements)
references
References 27 publications
5
108
0
Order By: Relevance
“…Detailed information about the sampling strategy and questionnaire design have been published previously. 17 19,20 The probability that youth in this category do not have an ASD is very low; however, not all youth with an ASD are identified in the autism category. Some may be served in other disability categories, may not be in special education, or may not attend school.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed information about the sampling strategy and questionnaire design have been published previously. 17 19,20 The probability that youth in this category do not have an ASD is very low; however, not all youth with an ASD are identified in the autism category. Some may be served in other disability categories, may not be in special education, or may not attend school.…”
Section: Methodsmentioning
confidence: 99%
“…The NLTS2 sampling plan was designed to produce weighted population estimates that are nationally representative of all students receiving special education services in the targeted age range and of students in each disability category. Full details of the weighting strategy for NLTS2 were previously published (Wagner et al 2005). The study reported here was approved by the University's Institutional Review Board.…”
Section: Study Samplementioning
confidence: 99%
“…Students with IEPs for special education services were then randomly selected from rosters of LEAs or special schools and weighted to yield nationally representative estimates that generalize to all students in the NLTS2 age range receiving special education services and to those in each special education disability category (Wagner, Kutash, Duchnowski, & Epstein, 2005).…”
Section: Study Databasementioning
confidence: 99%